2010
DOI: 10.1088/1742-6596/209/1/012002
|View full text |Cite
|
Sign up to set email alerts
|

Growth, structure and phase transitions of epitaxial nanowires of III-V semiconductors

Abstract: Abstract. We review and illustrate the impact of TEM on the study of nanowires of nonnitride III-V semiconductors, with particular emphasis on the understanding of the thermodynamics and kinetics of their formation assisted by nano-sized catalyst particles. Besides providing basic information about the morphology of the nanowires and their growth rate as a function of diameter, TEM offers insights into the peculiar crystalline structure that they adopt. We discuss the formation of the unusual wurtzite hexagona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
7
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 41 publications
1
7
0
Order By: Relevance
“…Phase transformation of grown GaAs NWs has been observed previously, where 2H structure epitaxially buried in planar 3C overgrowth gradually adopted the structure of the burying layer. 18 , 19 Phase transformation has also been observed in InGaAs NWs, using an electron beam to deliver a high energy dose to the structure, enough to transform 2H to a mixed 3C/2H structure. 20 In the case of epitaxial burying, one layer at a time of the metastable 2H is gradually surrounded with a layer of the stable 3C structure.…”
Section: Introductionmentioning
confidence: 99%
“…Phase transformation of grown GaAs NWs has been observed previously, where 2H structure epitaxially buried in planar 3C overgrowth gradually adopted the structure of the burying layer. 18 , 19 Phase transformation has also been observed in InGaAs NWs, using an electron beam to deliver a high energy dose to the structure, enough to transform 2H to a mixed 3C/2H structure. 20 In the case of epitaxial burying, one layer at a time of the metastable 2H is gradually surrounded with a layer of the stable 3C structure.…”
Section: Introductionmentioning
confidence: 99%
“…Since the pioneering works on semiconductor micro/nanowires spanning from the mid‐1960s to the early 2000s, the field of nanowire research has expanded exponentially to include numerous applications, supported by constant progress in the understanding of their fundamental growth mechanisms . Metal‐seeded III–V nanowires is an important group within the semiconductor nanowire family thanks to the maturity reached in terms of controlled growth, offering excellent properties of these materials, such as high carrier mobility, superior optical properties, and the possibility of band gap engineering …”
mentioning
confidence: 99%
“…In contrast, most studies which find predominantly WZ structure find a contact angle close to 90°(in cases where contact angle was shown or reported) 7,12,34,35 . In addition, a number of studies also found a greater density of ZB defects/regions near the foot of nanowires 12,16,36,37 . This is likely due to the fact that during the initial stages of nanowire growth the contact angle is much less than 90°, since the catalysing droplet is situated on a flat surface and the angle α in equation 2 is therefore equal to zero.…”
Section: Methodsmentioning
confidence: 98%